Perilaku Penelusuran Informasi di Perpustakaan Tingkat SMK - Chintya Almira; Aldi Priatmana; Pranindita Dwi Fadhila; Mehlan Ainul Firdaus; Franindya Purwaningtyas (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
Behavior to monitor information is said to be someone's action to find information in certain ways because some people will have several ways to access information, including for students in SMK. Efforts made to obtain information can be done in two ways, namely by manual method or by digitizing. The method that can be carried out by researchers is a type of library research research method using previous information to increase the relevance of the titles that the authors have chosen. The results showed that the efforts to meet the information needs were carried out by SMK students in two ways, namely by using the internet and by visiting the library manually. Keywords: behavior; information; search